METODE MENGAJAR BERVARIASI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Apriyanti Apriyanti (Universitas Muhammadiyah Lampung, 2020)
Various problems in the world of education still require concerted thinking efforts; one of these problems is in the field of mathematics studies in schools. This may be due to the way the lesson is delivered that is less effective, for that a teacher can create an interesting learning atmosphere so that it is not boring. A teacher must be able to choose a teaching system that is in accordance with the program of teaching and learning activities. In this study the method used is descriptive quantitative method, data analysis using statistical formulas. To find out student learning outcomes, the writer conducted an essay test. Based on the results obtained, it can be concluded that: